Arthroscopic Management of Dysplastic Hip Morphologies: Predictors of Success and Failures and Comparison to an Arthroscopic FAI Cohort. Issue 3 (23rd March 2015) - Larson, Christopher M.; Ross, James R.; Stone, Rebecca M.; Samuelson, Kathryn M.; Giveans, Russell; Bedi, Asheesh
Objectives: Previous reports regarding arthroscopic management of dysplastic hip morphologies have conflicting results. Arthroscopy alone in the setting of dysplastic morphologies is controversial. Methods: We retrospectively reviewed 88 hips (77 patients, 71% female, mean age 33.9 years) with radiographic findings consistent with hip dysplasia and a mean 26.0 months follow-up (range 12-80 months) after hip arthroscopy. Procedures performed included 67 labral repairs (76%), 20 selective labral debridements (23%), 72 capsular repair / plications (82%), and management of associated cam-type morphology in 63 hips (72%). All radiographs were evaluated for parameters consistent with dysplasia including the LCE, Neck Shaft angle, Tonnis angle, Extrusion index, femoral head lateralization, and break in Shenton's line. Preoperative and post-operative function were evaluated prospectively using the Modified Harris Hip Score (MHHS), SF-12 scoring, and pain on a visual analog score (VAS). Patient demographics, procedures performed, and radiographic parameters were evaluated with regards to functional outcomes. In addition, the results of the dysplastic cohort were compared to an aged matched cohort of 231 hips (215 patients, 52% female, mean age 32 years) performed during the study period with a mean follow-up 22.7 months (12-60 months) that underwent arthroscopic FAI correction without the diagnosis of dysplasia. Results: The mean LCE was 20.8 degrees (range, 8.7 - 24.5), and mean Tonnis angle was 11.0 (range, 0 - 22.2 degrees). The dysplastic cohort had a mean latest MHHS of 81.3 (range, 34-100) and mean 15.6 point (range, -28 - 60) improvement in MHHS compared to 88.4 points and 24.4 points, respectively, in the FAI cohort (p<0.01). The dysplastic cohort had 60.9% good to excellent results and 32.2% failures, compared to 81.2% good/excellent results and 10.5% failures for the FAI cohort (p<0.01). Decreased head neck offset (cam-type morphology) trended towards being predictive of better scores in the dysplastic cohort (p=0.079). In addition, dysplastic hips that underwent capsular plications and labral repairs had greater good / excellent results and lower failure rates (p>0.05). Grade 4 chondral defects were predictive of lower scores (p=0.02). There were no statistically significant differences for functional outcomes regarding gender or age for either cohort (p>0.05). There were no iatrogenic subluxations / dislocations in either group. Conclusion: Although functional scores were improved post-arthroscopy in hips with mild to borderline dysplastic morphologies, Good/Excellent results were inferior and Failure rates were higher compared to an FAI cohort. These results were independent of gender. Associated cam-type FAI, and labral repair / capsular plications were predictive of better clinical outcomes in the dysplastic cohort. Outcomes after pelvic osteotomy in this borderline population are required to determine the optimal treatment.